Risk factors of breast cancer in a sample of Kurdish women of Kurdistan region - Iraq: A comparative study between pre-menopausal and post-menopausal women - Zangana, Abdulqadir Maghded; Garota, Sherwan Ahmed (Zanco Journal of Medical Sciences (ZJMS), 2012)
Background and objective: To evaluate the difference between pre- and post-menopausal breast cancer regarding menstrual and reproductive risk factors for ca breast. Methods: A prospective case-control study was conducted in Nanakaly Oncology Hospital in Erbil city-Kurdistan- Iraq, between September 2009 and April 2011. Cases were breast cancer patients admitted in the oncology floor of the hospital. Controls were hospital patients without breast cancer (other cancers). The study enrolled 300 cases and 600 controls. Menstrual and reproductive history was taken from both the cases and the controls. For every risk factor age-adjusted odds ratio (OR) and 95% confidence interval (CI) was calculated by logistic regression analysis, separate for pre- and post-menopausal women. Results: Among the breast cancer patients, 42.7% were pre-menopausal and 57.3% were post-menopausal. Age at menarche had no association with breast cancer for both pre- and post-menopausal women. Nulliparity was a risk factor for both pre-menopausal (OR = 2.42, 95% CI (1.1-4.6) and post-menopausal breast cancer (OR = 3.7, 95% CI (2.04-6.87)). Among parous women only post-menopausal females having <3 children were at increased risk for breast cancer (OR = 2.18, 95% CL (1.45-3.27) compared with females having > 3 children. Younger age at first live birth decreased breast cancer risk in both pre- and post-menopausal women. Breastfeeding was not associated with both pre- and post-menopausal breast cancer. Conclusions: Majority of risk factors for pre-menopausal breast cancer are also associated with post-menopausal breast cancer except less parity, which increased the risk for post-menopausal breast cancer only.